Confocal Raman Microspectroscopy: A Non-Invasive Approach for in-Depth Analyses of Polymer Substrates - Tomba, Juan Pablo (2009)
We present a simple approach that avoids the problem of coupling fluid-sample interaction in confocal Raman depth-profiling with immersion objectives. We use a thin protective medium (polyethylene film) that preserves the sample from direct contact with the coupling fluid, and that can be readily attached/de-attached from the sample surface by applying a small difference of pressure. The strategy was tested performing confocal Raman depth profiling studies on a series of transparent substrates (polypropylene films; 25, 44 and 60 m nominal thickness) and comparing the results with those obtained with conventional approaches. It is shown that the strategy recovers very well all the film features, preserving at the same time a good depth resolution and optical throughput.